Elvis and His Blue Suede Shoes - Cox, Michael; Reeve, Philip (New York : Scholastic, 2001)
Everybody's heard of Elvis Presley. He is horribly famous for being the King of Rock'n'Roll, having trouble fitting into his spangly white jumpsuits and causing a riot with a wiggle of his pelvis. But not everyone knows that Elvis escaped from tornadoes by hiding in a cave, flew halfway across America for 22 giant sandwiches and had a tooth stuck in his lung... Everything you ever wanted to know about the man with the pelvis.
Keywords: History and Leaders -- non-fiction